Real Estate Price Inflation, Monetary Policy, and Expectations in the United States and Japan - Samiei, Hossein (IMF Working Papers; Working Paper ;, 1994)
During the mid- to late 1980s, inflationary pressures were highly concentrated in asset markets in many industrial countries. This paper discusses why this may have occurred and then develops a forward-looking supply and demand model of the real estate market in which equilibrium prices depend on price expectations, monetary conditions, income, returns to alternative assets, and construction costs. In this model, the current equilibrium price is determined by expectations formed in different time periods by consumers and producers. The model and its more generalized dynamic specifications are estimated by maximum-likelihood methods. The empirical results do not reject the view that the relationship between real estate values and monetary policy was altered in 1980s.